WAYS TO IMPROVE THE DIGITAL ECONOMY AND TRANSITION TO ELECTRONIC GOVERNMENT IN OUR COUNTRY (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article examines the mechanisms for implementing the tasks set in the Digital Uzbekistan 2030 Strategy. The development of the digital economy and e-government is substantiated, serious attention is paid to the IT sphere. At the same time, it is proposed to accelerate the implementation of modern digital technologies that meet the requirements of the present time.